An integrated look at the effect of structure on nutrient bioavailability in plant foods. (17th September 2018) - Capuano, Edoardo; Pellegrini, Nicoletta
Abstract: The true bioavailability of a nutrient being intrinsically coupled to the specific food matrix in which it occurs remains poorly considered in nutrition science. During digestion, the food matrix and, in particular, the structure of food modulate the extent and kinetics to which nutrients and bioactive compounds make themselves available for absorption. In this perspective, we describe an integrated look at the effect of structure on nutrient bioavailability in plant foods. Based on this integrated look, cell wall integrity and the particle size of the plant material during its transit in the small intestine determine the bioavailability of plant nutrients; in turn, cell wall integrity and particle size are determined by the level of oral processing and, accordingly, what subsequently escapes digestion in the upper intestine and is utilized by colon microbiota. Ultimately, the effect on nutrient digestion is linked to food structure through each step of digestion. A consideration of the structure rather than just the composition of foods opens up possibilities for the design of healthier foods. © 2018 Society of Chemical Industry